Pengaruh Metode Pendinginan Pasca Bakar Terhadap Perubahan Kuat Tekan Bata Ringan - I Gede Ngurah Swasti; Andi Marini Indriani; Gunaedy Utomo (Jurnal Konstruksi, 2026)
This study is motivated by the increasing use of lightweight bricks as a modern construction material due to their advantages, including low weight, good thermal insulation, and ease of installation. Foam agent-based lightweight bricks are made from a mixture of fine aggregate from Muara Samu sand, cement, water, and an air-foaming agent. The problem examined in this study is the degradation of material quality due to exposure to high temperatures during fire conditions, which may affect compressive strength. This study aims to determine the effect of burning duration and cooling methods on the compressive strength of lightweight bricks. The method used was a laboratory experiment employing cube specimens with a variation of 8 bar and 2 percent foam agent, which were burned for 20, 40, and 60 minutes. The specimens were then cooled using two methods: without water spraying and with water spraying, followed by compressive strength testing. The results indicate that the initial compressive strength was 1.89 MPa. After burning without water spraying, the compressive strength decreased to 1.53 MPa (20 minutes), 1.34 MPa (40 minutes), and 1.12 MPa (60 minutes). Meanwhile, with water spraying, the compressive strength decreased to 1.47 MPa (20 minutes), 1.28 MPa (40 minutes), and 1.04 MPa (60 minutes). The findings show that the longer the burning duration, the greater the reduction in compressive strength, and that the cooling method using water tends to accelerate the decrease in compressive strength.